2010
DOI: 10.1007/s11295-010-0332-8
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and molecular evidence of natural hybridization in Shorea (Dipterocarpaceae)

Abstract: Shorea (Dipterocarpaceae) is a large genus in which many closely related species often grow together in Southeast Asian lowland tropical rain forests. Many Shorea species share common pollinators, and earlier studies suggested occurrence of interspecific hybridization and introgression. Here, we show morphological and molecular evidence of hybridization between Shorea species. In the census of all the trees of Shorea curtisii, Shorea leprosula, and Shorea parvifolia (>30 cm dbh) within the 164-ha area of Bukit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
39
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 37 publications
(50 reference statements)
6
39
0
Order By: Relevance
“…From each population, material from 16 to 20 individuals were collected, except Bukit Larut and Lumut from which only seven and four individuals were obtained, respectively (Table 1). DNA samples from the Bukit Timah population used in this study were the same as those used by Kamiya et al (2011). The distance between sampled mother trees (or their saplings) was kept at 50 m or more to avoid the collection of half-sibs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…From each population, material from 16 to 20 individuals were collected, except Bukit Larut and Lumut from which only seven and four individuals were obtained, respectively (Table 1). DNA samples from the Bukit Timah population used in this study were the same as those used by Kamiya et al (2011). The distance between sampled mother trees (or their saplings) was kept at 50 m or more to avoid the collection of half-sibs.…”
Section: Methodsmentioning
confidence: 99%
“…In Lambir Hills, samples from 20 mature individuals > 30 cm diameter at breast height (dbh) were collected from the 52-ha ecologic-research plot (Lee et al 2002a). DNA samples from the Bukit Timah population used in this study were the same as those used by Kamiya et al (2011). Total DNA was extracted from fresh or dried tissue using the DNeasy Plant Mini Kit (QIAGEN, Valencia, California, U.S.A.) or a modified CTAB procedure implemented by Tsumura et al (1996).…”
Section: Methodsmentioning
confidence: 99%
“…In order to detect reticulation in the A. normale complex, we employed a biparentally inherited marker, the single-copy nuclear gene pgiC. The pgiC gene has recently been successfully used in several phylogenetic studies of hybridization in ferns as well as in flowering plants (Russel & al., 2010;Juslen & al., 2011;Kamiya & al., 2011;Dyer & al., 2012;Sessa & al., 2012;Wang & al., 2012). Additionally, ploidy levels of the samples were determined by measuring spore size (Barrington & Paris, 1986) and determining DNA C-values by flow-cytometric analysis of selected specimens (Dolezel & al., 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it was previously 460 suggested that inter-specific hybrids between rainforest tree species are poor competitors, and that 461 fertile hybrid populations are nearly non-existent (Ashton 1969). While there is some evidence of 462 introgression in tropical trees (Scotti-Saintagne et al, 2013), most available studies substantiating this 463 are based on trees from other tropical regions or habitats (e.g., Shorea in Asia (Kamiya et al, 2011;464 Kenzo et al, 2019), or Rhizophora in Indo-Pacific mangroves (Lo 2010)). Many of these other 465 instances appear to occur only in degraded habitats, or involve infertile first-generation hybrids with 466 minimal backcrossing, which contrasts with the findings of our study.…”
Section: The Contribution Of Hybridization To Neotropical Rainforest mentioning
confidence: 99%